PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN NARKOBA - MARIAH SONANGGOK M PURBA (LP2MTBM MAKARIOZ, 2018)
Turnover from time to time in this latest development, the use of illegal drugs in Indonesia should not be underestimated as illustrating the seriousness that is already worrying, pleasing to commemorate the commemoration of the Anti-Madat World on June 26, 2002 that drug problems in Indonesia are described in color yellow, while psychotropic problems are described in red. Drug abuse has become a universal problem, because many countries experience a serious problem and this crime is very much related to organizational crime and money laundering, as the abuse is very detrimental to the nation and state Given the complexity of drug problems, a method and strategy is needed to mitigate drugs. The eradication strategy in addition to implementing national and international regulations on drugs, also needs law enforcement against the perpetrators.